Making a difference : feminist literary criticism - Greene, Gayle, 1943-; Kahn, Coppélia (New accents (Routledge (Firm)), 1991)
An invaluable overview of feminist critical thinking. The esssays address a wide range of topics including: the politics of language; feminist readings of the canon; psychoanalysis and feminism; French theories of the feminine.